Nutrient Partitioning and Dynamics in Coriaria nepalensis Wall Dominated Shrublands of Degraded Hills of Kumaun Himalaya - Awasthi, Pankaj; Bargali, Kiran; Bargali, Surendra Singh; Khatri, Kavita; Jhariya, Manoj Kumar (Frontiers in Forests and Global Change, 2022)
Coriaria nepalensis is one of the shrubs which have the ability to mitigate the frequency of perilous natural events or natural calamities. This paper elucidates the nutrient dynamics of C. nepalensis shrublands in degraded hills of Kumaun Himalaya. The average nutrient concentration (N, P, and K) in aboveground components of C. nepalensis was in the following order: Foliage > Twigs > Branches > Bole wood, whereas in belowground components the order was: Fine roots > Lateral roots > Stump root. The order of contribution to total nutrient storage in vegetation was: Tree > Herbs > Shrubs. The proportion of nutrients stored in the shrub layer was in the order: N > K > P. The soil stored a maximum proportion of nutrients at each site (79.48–87.54% N, 70.47–87.88% P, 74.33–88.27% K). Maximum nutrient storage in soil and vegetation was recorded for site 3 (Barapatthar) and minimum for site 1 (Pines). The uptake of N, P, and K by vegetation ranged from 428 to 1,353 kg ha–1 yr–1, 32–102 kg ha–1 yr–1, and 109–479 kg ha–1 yr–1, respectively. In the present study, the turnover time was 1.06–1.33 years for N, 1.03–1.15 years for P, and 1.02–1.13 years for K. Compartment models reflect the distribution of nutrients and net annual flux that will help to develop the management plan to maintain the fertility and productiveness of the degraded sites.